2020
DOI: 10.31983/jahmt.v2i1.5475
|View full text |Cite
|
Sign up to set email alerts
|

Tedi’s Behavior Change Model to Improving Brushing Teeth Behavior Parents

Abstract: The dental health problems of preschool children are higher compared to primary schools, this is due to children not being able to do independent activities in brushing their teeth. The right behavior change strategy can be carried out by providing dental health education by parents and teachers using learning methods and media tailored to the child's development. Tedi's behavior change is a model of learning to brush teeth in an effort to establish preschooler brushing behavior with 10 days. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Attitudes can be formed when someone obtains information, provides feedback and will take action after being given the information. 31 The results of the unpaired data effectiveness test of the attitude pre-test showed that the p-value of the intervention group and the control group was 0.290, which means there was no significant difference, but in the attitude post-test the pvalue was 0.004 (p <0.05), which means that there is a significant difference so that it can be concluded that the "Fule's version of the Fule's version of the traditional game modification game" is more effective in increasing children's knowledge compared to flipchart media.…”
Section: Discusionmentioning
confidence: 99%
“…Attitudes can be formed when someone obtains information, provides feedback and will take action after being given the information. 31 The results of the unpaired data effectiveness test of the attitude pre-test showed that the p-value of the intervention group and the control group was 0.290, which means there was no significant difference, but in the attitude post-test the pvalue was 0.004 (p <0.05), which means that there is a significant difference so that it can be concluded that the "Fule's version of the Fule's version of the traditional game modification game" is more effective in increasing children's knowledge compared to flipchart media.…”
Section: Discusionmentioning
confidence: 99%
“…This kesgi pillow book media made with colorful and attractive colors will make dental health education fun and of course the material taught will be easily absorbed by children. 7,14 The advantages of the pillow book media as a promotion of dental and oral health include; the nature of the media is durable because it is made of cloth so that it is not easily dirty, wrinkled, or torn; easy to understand because real pictures of learning become fun because of the many colors, lots of activities, and provoke children's creativity to do the existing activities to be better and systematic; practical, because in one book there are various kinds of activities that support children's fine motor skills and are easy to carry everywhere. 10 The hope of the Kesgi pillow book education model is an increase in tooth brushing skills in preschool children which can ultimately improve the dental health status of preschool children.…”
Section: Discusionmentioning
confidence: 99%
“…In general, the target of dental health programs in schools is elementary school children, so that dental health programs for preschool children do not get serious attention and are less than optimal. [5][6][7] Seeing this, it is still very important to carry out various innovations and breakthroughs to prevent dental caries, one of which is by innovative dental health education models that can make schools independent in preventing dental disease. This is in accordance with a government program that recommends the implementation of brushing teeth every day at school for preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian terdahulu menyatakan bahwa orang tua yang diberikan pelatihan dengan tujuan meningkatkan perilaku berupa pengetahuan, sikap dan tindakan akan mampu untuk mentransfer pengetahuan dan dapat meningkatkan keterampilan pada anak. [16] Pembimbingan dan pendampingan orang tua khususnya ibu kepada anak dalam rangka menjaga kebersihan gigi dan mulut sangat diperlukan sebagai role model. Peran serta orang tua dibutuhkan dalam memberikan bimbingan, pengertian, mengingatkan dan menyediakan keperluan dalam menggosok gigi sehingga anak dapat dengan mudah melakukan gosok gigi serta dapat memelihara kesehatan gigi dan mulutnya, maka dari itu ibu mempunyai peran penting untuk memberikan pengaruh dalam meningkatkan keterampilan menggosok gigi.…”
Section: Metode Penelitianunclassified